Research understanding of pluralism definition of "consumer society" - Старицька, Ольга Олексіївна; Ацикян, Арсен Робертович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In this article the authors examined pluralism of definition of "consumer society". The analysis of the current legislation on these issues, and examined the scientific vision of the appointed term.